Circulating microRNAs as Biomarkers for Breast Cancer Brain Metastasis - Sereno, Marta Bruno Soares de Melo (2021)
Tese de mestrado, Ciências Biofarmacêuticas, Universidade de Lisboa, Faculdade de Farmácia, 2018